Balanced Asset Allocation How to Profit in Any Economic Climate - Shahidi, Alex (Wiley Finance, 2014)
The conventional portfolio is prone to frequent and potentially devastating losses because it is NOT balanced to different economic outcomes. In contrast, a truly balanced portfolio can help investors reduce risk and more reliably achieve their objectives. This simple fact would surprise most investors, from beginners to professionals. Investment consultant Alex Shahidi puts his 15 years of experience advising the most sophisticated investors in the world and managing multi-billion dollar portfolios to work in this important resource for investors. You will better understand why nearly every portfolio is poorly balanced and how to view the crucial asset allocation decision from a deeper, more thoughtful perspective. The concepts presented are simple, intuitive and easy to implement for every investor. Author Alex Shahidi will walk you through the logic behind the balanced portfolio framework and provide step-by-step instructions on how to build a truly balanced portfolio. No book has ever been written that discusses asset allocation in this light. Provides insights from a top-ranked investment consultant using strategies from the industry's brightest minds Proposes a balanced asset allocation that can achieve stable returns through various economic climates Introduces sophisticated concepts in very simple terms For those who want to better manage their investment portfolio and seek a more advanced approach to building a balanced portfolio, Balanced Asset Allocation: How to Profit in Any Economic Climate provides an in-depth treatment of the topic that can be put to use immediately